Evaluating personnel evacuation risks under fire scenario of Airbus wide-body aircraft: A simulation study - Wei Lv; Luliang Xing; Jiawei Li; Caihong Zhao; Yunpeng Yang (Frontiers Media S.A., 2022)
Airliner accidents are often accompanied by incidental aircraft fires, causing huge casualties and incalculable economic losses. The research on airliner fire and its emergency evacuation is the focus and difficulty of aviation safety research, but it is difficult to carry out the research through experiments, and the use of computer simulation is an effective method. This paper comprehensively studies the dynamic development of the cabin fire and the corresponding cabin evacuation when the wide-body airliner Airbus A350-900 is forced to land in two states: horizontal and forward. The spatial distribution of the remaining evacuation time at each seat is used to analyze and judge the safety evacuation risk of the airliner cabin. Finally, two evacuation optimization design ideas based on partition guidance and seat layout are proposed to improve the spatial distribution of the overall evacuation risk of passengers in the cabin and provide some reference suggestions for strengthening fire prevention in the design, manufacture, and use of airliner. Some targeted countermeasures are put forward for the emergency evacuation of passengers in the cabin in a fire situation.